Limb salvage and complication management after (sub-) total humerus resection for primary malignant bone tumors in early childhood - Wiebke K. Guder; Nina M. Engel; Jendrik Hardes; Lars E. Podleska; Dimosthenis Andreou; Markus Nottrott; Arne Streitbürger (Journal of Orthopaedic Surgery and Research)
Abstract Limb-salvage after (sub-) total humerus resection in skeletally immature patients, aged less than 10 years, remains the domain of individual case decisions due to a small number of affected patients. Seven children aged ≤ 10 years at the time of (sub-) total bone sarcoma resection of the humerus between 2018 and 2023 were included in this retrospective study. Limb salvage with an intact motor function of the lower arm was achieved in 100% of cases at a mean follow-up of 89.8 months. Reconstruction survival was 28.6%. 61.8% (n = 8/13) of complications necessitated revision operations (n = 7). Distal instability and dislocation (n = 5) was the most frequently observed complication, followed by periprosthetic infection (n = 2). However, both fixed hinge prostheses and hemiprostheses with a highly cancellous implant body led to stable reconstructions of the elbow joint. Arm lengthening (5 cm) was successful in two patients who underwent implantation of a growing prosthesis. Patients developed a handedness contralateral to the operated arm in this study. The mean MSTS and TESS scores were 16.6 and 51.5. Patients suffered from a limited range of motion in the glenohumeral joint, limited fine motor function and strength despite an intact innervation of the executing muscles. Salvage of even short segments of the distal humerus has a high potential to decrease complication rates, whenever oncologically feasible. The use of fixed-hinge total humerus (growing) prostheses and custom-made total humerus hemiprostheses with a highly cancellous implant body showed the most promising results in terms of complications and functional outcomes. Arm lengthening using growing prostheses - albeit of a mostly cosmetic value - is an option in the upper extremity whenever the soft tissue coverage of the implant is adequate.